SUMBANGAN KECEPATAN TERHADAP PRESTASI LOMPAT JAUH - SISWO SURYANTO (STKIP Paris Barantai, 2010)
This research will look for an alternative of answer about contribution of speed to achievement of long jump. To find the answer, Writer does research to 40 Study Students of programe Penjaskesrek in 1999 STKIP PARIS BARANTAI KOTABARU. In this research entangles one independent variables that is speed and one dependent variableses that is achievement of long jump. Analysis applied is correlation. Starting from the problems, hence purpose of which will be reached in this research in general is wish to know contribution of speed to achievement of long jump which is one of number jumps at athletic athletics branch. As for peculiarly purpose of this research is to know